On Fractional Derivatives and Primitives of Periodic Functions. (14th August 2014) - Area, I.; Losada, J.; Nieto, J. J.
Abstract : We prove that the fractional derivative or the fractional primitive of aT -periodic function cannot be aT -periodic function, for any periodT , with the exception of the zero function.